2016
DOI: 10.1007/s12649-016-9614-1
|View full text |Cite
|
Sign up to set email alerts
|

Solar Greenhouse Drying of Wastewater Sludges Under Arid Climate

Abstract: Wastewater sludges were dried in an open greenhouse pilot in order to provide experimental data about solar greenhouse drying under an arid climate during hot and cold periods. Climatic conditions, solids contents and geometric dimensions were constantly measured. The shape change of samples was constantly recorded with digital scan. The results indicated that solar greenhouse drying reduced the moisture content from about 4 kg water/kg DS to 0.08 kg water/kg DS in hot period and to 0.2 kg water/kg DS in cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This result is logical as the sludge was thickened before being dried. Other studies 11,16 have shown the same result. In winter, the variation in the drying rate curves is irregular for all the experiences regardless of the air flow rate.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This result is logical as the sludge was thickened before being dried. Other studies 11,16 have shown the same result. In winter, the variation in the drying rate curves is irregular for all the experiences regardless of the air flow rate.…”
Section: Resultssupporting
confidence: 74%
“…One of them was equipped with a gravel floor where hot water, generated by a solar collector, was circulated. Belloulid et al 11 have aimed to provide experimental data about solar drying under an arid climate using an open greenhouse. Therefore, these studies present the results of the utilization of the drying bed or the greenhouse on the sludge drying characteristics in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted by researchers to improve the performance of GHDs. Some of these advancements are their integration with PV modules [26,50,52,[70][71][72][73][74]; application of an opaque north wall to hamper heat loss from the dryer to ambient [75][76][77][78][79]; integration of thermal storage materials i.e., sand, phase change materials (PCMs), rockbed and black colored concrete floor [80][81][82][83]; integration of solar air heaters for faster drying [27,84]; and adding a supplementary area for drying area augmentation [85]. In this section, we discuss the most common technologies that are integrated with GHDs to improve their thermal efficiency, decrease the drying time, and increase the quality of the final product.…”
Section: Solar-assisted Greenhouse Dryers (Sghds)mentioning
confidence: 99%
“…Sludge treatment is a combination of technically feasible, economically efficient and socially acceptable ways. It is probable, and even certain, that the current outlets will change in the years to come as a result of new regulatory requirements adopted primarily to regain confidence from the general public [7]. In this context, the upstream treatment of sludge, whose purpose is to condition the collected sludge in a form compatible with its intended use.…”
Section: Introductionmentioning
confidence: 99%